Pengaruh Kompensasi dan Pengembangan Karir Terhadap Kepuasan Kerja (Studi Pada Karyawan Departemen PPIC PT. Shoetown Ligung Indonesia) - Kusumadewi, R. Neny; Suparto, L; Rusdiana, Alan; Foezi Hadi Suarno, Tino (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
Human resources are an important element in an organization, especially for business organizations. Therefore, many companies are starting to seriously build and develop their human resources. Considering the importance of human resources in an organization, companies must pay attention to employee satisfaction. Job satisfaction is also related to outcomes such as performance, so that if job satisfaction is higher it will create enthusiasm for work. The aim of this research is to identify the influence of compensation and career development on job satisfaction. The population in this study were employees of the PPIC department of PT. Shoetown Ligung Indonesia, numbering 305 people. The research sample consisted of 100 people taken using purposive sampling technique. The data analysis method is multiple linear regression analysis using SPSS 26. The results of this research state that compensation and career development have a positive and significant effect on job satisfaction, both partially and simultaneously